A Bayesian Approach to Sport Injuries Likelihood: Does Player’s Self-Efficacy and Environmental Factors Plays the Main Role? - Olmedilla, Aurelio; Rubio, Víctor J.; Fuster-Parra, Pilar; Pujals, Constanza; García-Mas, Alexandre (Frontiers in Psychology, 2018)
The psychological factors of sports injuries constitute a growing field of study, even from the point of view of the prediction of their occurrence. Most of them, however, do not take into account the likelihood of the lesions’ occurrence and the weight and role of the psychological variables on it. We conducted a study building up a Bayesian Network on a big sample of athletes, trying to assess these probabilistic links among several relevant psychological variables and the injuries’ occurrence. The sample was constituted by 297 athletes (239 males, 58 females) from a wide range of sports: track and field; judo; fencing; karate; boxing; swimming; kayaking; artistic rollerskating, and team sports as football, basketball and handball (Mean age: 25.10, +- 3.87; Range: 21 – 38 years). Several psychological variables, such as anxiety, social support, and self-efficacy were studied. Also, we recorded the injuries record as well the BMI and personal epidemiological data. The overall picture of the generated graph and Bayesian Network and its analysis –including the use of hypothetical data by means of several instantiations- includes the nuclear role of the Self-Efficacy regarding the injuries’ occurrence likelihood; the decreasing impact of the competitive anxiety previous to the injury; the probabilistic independence of the players’ risk behaviors, and the relevance of the environmental clues such the use of coping strategies and social support in order to build up a good level of Self-Efficacy after the occurrence of an injury. All these data are relevant when designing both preventive and recovery interventions from the multidisciplinary as well as the psychological point of view.